2008
DOI: 10.1021/ja807611n
|View full text |Cite
|
Sign up to set email alerts
|

Microcontact Printing of Dendrimers, Proteins, and Nanoparticles by Porous Stamps

Abstract: Porous stamps fabricated by one-step phase separation micromolding were used for microcontact printing of polar inks, in particular aqueous solutions of dendrimers, proteins, and nanoparticles. Permanent hydrophilicity was achieved without any additional treatment by tailored choice of the polymer components. Pores with several hundred nanometers to micrometers were obtained during the phase separation process. These pores can act as ink reservoirs. The porous stamps were thoroughly characterized by SEM, NMR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…Many methods, including lithography, microcontact printing, phase separation, solution casting/ salt leaching, freeze-immersion, emulsion freeze-drying, gel casting, gas foaming, and colloidal assemblies as templates, are introduced to generate the porous films [8][9][10][11][12][13][14][15]. In particular, François et al [16,17] have first reported an attractive breath figures (BFs) approach to prepare microporous films with regular honeycomb pores by casting star polystyrene (SPS) and poly(para-phenylene)-block-PS (PPS) polymer solutions under humid air flow.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods, including lithography, microcontact printing, phase separation, solution casting/ salt leaching, freeze-immersion, emulsion freeze-drying, gel casting, gas foaming, and colloidal assemblies as templates, are introduced to generate the porous films [8][9][10][11][12][13][14][15]. In particular, François et al [16,17] have first reported an attractive breath figures (BFs) approach to prepare microporous films with regular honeycomb pores by casting star polystyrene (SPS) and poly(para-phenylene)-block-PS (PPS) polymer solutions under humid air flow.…”
Section: Introductionmentioning
confidence: 99%
“…S urface modification has become a critical component of micro-and nanofabrication with applications in technologies ranging from biodetection 1,2 to catalysis 3,4 and many more [5][6][7][8] . Many of these applications exploit non-covalent interactions and molecular recognition.…”
mentioning
confidence: 99%
“…实现图案化的方法有光刻蚀法 [4] 、电子束刻蚀 法 [5,6] 、微接触转印法 [7,8] 以及喷墨打印法 [9,10] The dashed line indicates the initial position of the printed gold nanoparticle ink before dewetting from the hydrophobic surface layer on the first electrode. Atomic force microscopy (2 μm×2 μm) (b) and scanning electron microscopy (c) image of the short channel between a printed second and an evaporated first gold electrode.…”
Section: 引言mentioning
confidence: 99%